2022
DOI: 10.1039/d1dt03647e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of water-dispersible Janus nanosheets from K4Nb6O17·3H2O and their behaviour as a two-dimensional surfactant on air–water and water-toluene interfaces

Abstract: K4Nb6O17·3H2O-based Janus nanosheets with water dispersibility and surface activity were prepared via sequential regioselective surface modification. To provide individual Janus nanosheets with these two properties, phenylphosphonic acid and phosphoric acid...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…K 4 Nb 6 O 17 ·3H 2 O-based Janus nanosheets with surface activity were also reported. 111 Janus nanosheets bearing a hydrophilic dihydroxyphosphonate moiety and a hydrophobic phenylphosphonic moiety showed a slower decrease in surface tension at an air–water interface than that achieved with molecular surfactants. In an emulsion of toluene and aqueous Janus dispersion, unique coalescence and Ostwald ripening behaviour was also observed.…”
Section: Janus Nanosheets Based On Clay Minerals and Ion-exchangeable...mentioning
confidence: 83%
See 1 more Smart Citation
“…K 4 Nb 6 O 17 ·3H 2 O-based Janus nanosheets with surface activity were also reported. 111 Janus nanosheets bearing a hydrophilic dihydroxyphosphonate moiety and a hydrophobic phenylphosphonic moiety showed a slower decrease in surface tension at an air–water interface than that achieved with molecular surfactants. In an emulsion of toluene and aqueous Janus dispersion, unique coalescence and Ostwald ripening behaviour was also observed.…”
Section: Janus Nanosheets Based On Clay Minerals and Ion-exchangeable...mentioning
confidence: 83%
“…The results showed that Janus nanosheets with relatively hydrophilic surface functional groups on both sides can be initially dispersed as single-layered nanosheets, but then form aggregates after standing for a few months. 111 It was also reported that the structures of graphene-based Janus nanosheets were converted into double-layered structures with a hydrophobic internal space and hydrophilic external surfaces in water. 77 The dispersibility of Janus nanosheets bearing two types of stimuli-responsive polymers on two surfaces could be controlled, moreover, by two types of stimuli, such as changing temperature and pH.…”
Section: Discussionmentioning
confidence: 99%